National Adaptation Planning Lessons from OECD Countries - Mullan, Michael (OECD Environment Working Papers, 2013)
Since the first OECD country published its national adaptation strategy in 2005, there has been a marked increase in national planning for climate change adaptation. This paper provides an overview of national adaptation planning activity across OECD countries and identifies some of the emerging lessons that have been learnt from their experiences. The analysis draws on three main sources of information: a survey of countries' national communications to the UN Framework Convention on Climate Change (UNFCCC); three country case studies (Mexico, England and the United States); and the results of a Policy Forum on Adaptation hosted by the OECD in 2012. It finds that twenty-six OECD countries have developed or are currently developing strategic frameworks for national adaptation and seventeen of those countries have also produced or are working on detailed national adaptation plans.